2019 IEEE Symposium on Security and Privacy (SP) 2019
DOI: 10.1109/sp.2019.00011
|View full text |Cite
|
Sign up to set email alerts
|

Resident Evil: Understanding Residential IP Proxy as a Dark Service

Abstract: An emerging Internet business is residential proxy (RESIP) as a service, in which a provider utilizes the hosts within residential networks (in contrast to those running in a datacenter) to relay their customers' traffic, in an attempt to avoid serverside blocking and detection. With the prominent roles the services could play in the underground business world, little has been done to understand whether they are indeed involved in Cybercrimes and how they operate, due to the challenges in identifying their RES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 22 publications
0
40
1
Order By: Relevance
“…Some services can also detect the use of VPNs, adding information to enable tracking, and even block them, such as Netflix who attempts to geo-lock their content. Finally, users must also trust the VPN service since they are ideally positioned for snooping the users' activities, as has been shown in existing work [21].…”
Section: Discussionmentioning
confidence: 99%
“…Some services can also detect the use of VPNs, adding information to enable tracking, and even block them, such as Netflix who attempts to geo-lock their content. Finally, users must also trust the VPN service since they are ideally positioned for snooping the users' activities, as has been shown in existing work [21].…”
Section: Discussionmentioning
confidence: 99%
“…While we could have used residential proxy services to acquire more residential IP addresses, this approach still has several drawbacks. Mi et al [37] showed that a majority of the devices proposed by residential proxy services did not give their consent. Moreover, since residential proxy services do not provide mechanisms to ensure the nature of the device that will act as a proxy, there can be inconsistencies between the browser fingerprint of our crawlers and the TCP or TLS fingerprints of the proxy, making it more difficult to understand why a crawler was blocked.…”
Section: ) Crawler Familymentioning
confidence: 99%
“…Residential Proxy. The first study examining the behavior of the residential proxies is due to Mi et al [8], where the authors conducted an in-depth analysis on residential proxy services and servers, including about six million residential IP addresses across ≈230 countries and 52,000 Internet Service Providers (ISPs). Their findings show that even though residential proxy providers claim that the proxy hosts willingly participated in providing the service, many proxies operate on compromised hosts.…”
Section: Related Workmentioning
confidence: 99%
“…Residential proxies are not public, so it is difficult to obtain their IP addresses in a similar way. To this end, we obtained the dataset residential proxies from Mi et al [8]. Mi et al utilized an infiltration framework to collect a dataset of 6,419,987 residential proxies distributed across more than 230 countries and more than 52,000 ISPs.…”
Section: Data Collection and Measurement A Proxy Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation